Comparison of Surface Roughness of Nanohybrid Composite Resin Immersed in Various Mouthwashes - Rina Permatasari; Kianti Islamiah (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Surface roughness is a contributing factor to the accumulation of plaque and the development of secondary caries, also can determine the aesthetic and long-term durability of dental restoration materials, such as nanohybrid composite resin. The use of mouthwash is one of the factors that cause the surface roughness of nanohybrid composite resin. Material and Methods: The research method used was laboratory experimental research with a pre-test and post-test design. Thirty samples of nanohybrid composite resin were randomly divided into three treatment groups (n=10) according to the types of mouthwash (alcohol-containing, alcohol-free, and herbal), and then were immersed for 36 hours. Surface roughness measurements were performed with a surface roughness tester before and after treatment. Results and Discussions: One-way ANOVA statistical analysis showed a significant difference (p<0,05) in all treatment groups. Conclusion: The highest surface roughness was found in alcohol-containing mouthwash, followed by alcohol-free mouthwash and herbal mouthwash.